The Effect of Tomato Juice in Increasing Ki-67 Expression and Epithelial Thickness on The Vaginal Wall of Menopausal Rats - Juminten Saimin; Hendy Hendarto; Soetjipto Soetjipto (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Dyspareunia and pain due to the decrease of vaginal wall thickness usually happen in menopausal women. The reduction of estrogen levels cause the decreasing of cell proliferation and the thinning of vaginal wall epithelium. Tomato (Solanum lycopersicum) is a source of phytoestrogens, which produce estrogenic effects. This study aims to assess the effect of tomato juice on Ki-67 expression and epithelial thickness of the vaginal wall in menopausal rats.METHODS: This was an experimental study using Sprague-Dawley rats. Twenty-four female rats, aged 4 months and weighing 150-200 grams, were divided into 4 groups. Each group consisted of 6 rats. Negative control (NC) group was group of rats with sham procedure and performed by distilled water for 28 days. Positive control (PC) group was group of bilateral ovariectomized rats and performed by distilled water for 28 days. The first treatment (T1) group was group of bilateral ovariectomized rats, given tomato juice at dose of 11g/200g body weight (BW)/day. The second treatment (T2) group was group of bilateral ovariectomized rats, given tomato juice at dose of 15g/200g BW/day. Data analysis was done with Anova, multiple comparisons and regression test.RESULTS: The group with lowest Ki-67 expression was PC group (2.52±0.60). The expression of Ki-67 in treatment groups (T1 and T2) was higher than PC group, but lower than NC group. There was no significant difference between groups (p=0.771). The lowest epithelial thickness was found in PC group (21.19±3.96) and the highest was found in the treatment groups (38.73±12.43). There was positive correlation between tomato juice and epithelial thickness (p=0.647).CONCLUSION: Tomato juice increases Ki-67 expression and epithelial thickness on the vaginal wall of menopausal rats. The increase of epithelial thickness follows the administration dose, but Ki-67 expression does not exceed in the control rats. Tomato juice increases the cell proliferation of vaginal wall on menopausal rats, however the increase is still within normal limits.KEYWORDS: epithelial thickness, Ki-67, menopause, tomato juice